The law applicable to electronic negotiation disputes - Hassan, prof. Dr. Muhammad Jalal Hassan; Radha, Asst. Prof. Dr. Afan Abdel Aziz Radha (Sulaimani Journal for Humanities, 2025)
Due to the development of modern electronic means of communication and their role in the field of international trade, the number of deals and contracts concluded has increased, especially those contracts of great financial importance, and thus the importance of contract negotiation has increased at the international and national levels, as it has become an indispensable necessity in order to reach the conclusion of the contract and stabilize the transactions. Accordingly, the negotiation stage is considered one of the most important and dangerous stages, as preparation and preparation for concluding the contract take place and all its technical, financial and legal aspects are discussed, as are the expected difficulties during its implementation and methods for addressing them within a specific and accompanying strategy based on negotiation skills, in addition to finding appropriate solutions to them and determining the rights and obligations of the parties and the scope of responsibility. The consequences of breaching these obligations, in addition to determining the law applicable to the contract, especially if it is of an international nature, such as if it includes a foreign element, such that one of the parties to the negotiation is a foreigner or it takes place in a foreign country. Usually, the problem of dispute over negotiation arises due to the lack of an explicit agreement between the two parties on it. Then the dispute arises, and the judge, when deciding it, searches for the disputed relationship and adapts it according to the law, and then searches for the rule of attribution under which the dispute falls in order to determine the applicable law.
Keywords: Contract negotiation; electronic contracts; international trade; modern means of communication